الرموز الإغريقية في مسرحية شكسبير (أنتوني وكليوباترا) - طـه, أحمد (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
This study aims at examining the various cultural and intellectual aspects of the human thinking, which dates years back in history. The human thinking was best embodied in Mythology, where the Greeks incarnated the various aspect of human nature in the characters of Apollo and Dionysus. They found in the character of these two gods a true refection for the instinct and natures inborn in Man; so, they believed that they represent the source of all these natures. Shakespeare in his Antony and Cleopatra embodies all these aspects associated in Greek Mythology with Apollo, like "light", "youth", "sun", "reason", and "culture", in Antony; and he incarnates all these natures associated with Dionysus, like "permissiveness", "vegetation", "instinct", "primitive" nature", and "wine", in the character of Cleopatra. Shakespeare intentionally does not give precedence to either Antony or Cleopatra, striking a balance between their two natures. In doing so, he reassures that human nature is an amalgamation of two different natures inborn in man. None of these natures may be given precedence over the other, as Apollonianism versus Dionysiunism in ways of conduct and course of movement, but it is consonant with it in its predestinations. In this sense, the polarity in the play "becomes perfection" by the lover's devoted love. Thus, Shakespeare justifies the ways of the world to man, rather than denying them the right to exit. يهدف البحث إلى إبراز الأصول الفكرية والإنسانية المتجذرة في التاريخ بأشكال شتى، وخاصة الأسطورة بما فيها من أفكار نسجها الخيال الإنساني لتصبح مرآة تعكس واقع الطبيعة البشرية بخيرها وشرها. يجسد قدماء الإغريق طبائع البشر المتمثلة "بالضوء"، "والشباب"، "والشمس"، "والعقل"، "والثقافة" "والخمر" بأبوللو ويجسدون عناصر "الغريزة"، "والنمو"، "والطبيعة البدائية"، "والانحلال"، والخمر في شخصية ديونيسوس، ويصنفون البشر على أساس هذه الطبائع والغرائز التي يعتقدون بأن أصولها تعود إلى هاتين الآلهتين. يجسد شكسبير هذه الأفكار في شخصية أنتوني وكليوباترا، حيث يقدم كليوباترا صورة مصغرة للإله ديونيسيوس, وذلك بتصرفاتها، وحبها للحياة، والخمر، واللهو، والمرح، واتباعها للغريزة والشهوانية، ويصور أنتوني نداً لأبوللو، بحكمته، وعقله، وثقافته، وشبابه، وحبه للحياة والضوء، والقوة، والسلطة والاتزان. وبالتالي يؤكد شكسبير بأن الفكر البشري قديماً وحديثاً شيء متواصل وإن اختلفت المتسميات فإن الأصول الفكرية واحدة، والغرائز والطبائع واحدة، وبالتالي فإن البشر مهما اختلفت مشاربهم فإن أصولهم الفكرية متجانسة. ينتهي البحث بالوصول إلى نتيجة هامة حول فشل أي من الطبيعيتين المشار إليهما أعلاه في التغلب على الأخرى حيث يفشل أنتوني في تحقيق نصر نهائي على كليوباترا، وتفشل كليوباترا بتحقيق نصر نهائي على أنتوني. ومن هنا تبرز أهمية خلق توازن بين الطبيعيتين، طبيعة حب الحياة من جهة، وغريزة العقل والحكمة من جهة أخرى، لأن الطبيعة البشرية هي خليط من هذه الغرائز جميعاً، وتبقى هذه الطبيعة ناقصة إذا ما سيطر عنصر من هذه العناصر على الآخر وأزاله من الوجود.